Positive pole piece as well as preparation method and application thereof
By using polyvinylidene fluoride hexafluoropropylene (PVDF-HFP) as the binder in the active layer of the positive electrode sheet, the problems of powder loss and peeling force reduction in nano-mixed lithium manganese iron phosphate positive electrode material during the process are solved, and the peeling force of the nano-mixed lithium manganese iron phosphate positive electrode material is achieved. Higher peeling force, bending and electrochemical properties.
Patent Information
- Application Number
- CN202411538860.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, nano-lithium manganese iron phosphate (LMFP) cathode material has problems such as powder loss, reduced peeling force, and increased brittleness during the process, which affects battery performance.
The new binder polyvinylidene fluoride hexafluoropropylene (PVDF-HFP) is introduced into the active layer of the positive electrode sheet. The crystallinity of the binder is reduced through its perfluorinated segment, the specific surface area is increased, and the adhesion is improved. Peeling force.
It effectively improves the peeling force, bending and stability of the positive electrode sheet, reduces brittleness and interface resistance, and improves electrochemical performance. It is suitable for the preparation of positive electrode sheets of nano-polymer lithium manganese ferrophosphate materials.
Smart Images

Figure CN119419274A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode sheet and a preparation method and use thereof. Background Art
[0002] As a rapidly developing clean energy in the 21st century, lithium-ion batteries play an important role in portable electronic devices, new energy vehicles and even large-scale energy storage systems due to their advantages such as high energy density and long cycle life. With the continuous expansion of the new energy vehicle market and the diversification of application scenarios, the demand for batteries with high power, high specific energy and long life is becoming increasingly urgent, which brings more challenges to the development of lithium-ion battery technology.
[0003] As the core component of lithium-ion batteries, cathode materials have a decisive influence on the electrochemical performance of batteries. They directly determine key performance indicators such as battery charge and discharge capacity, cycle life, platform voltage, self-discharge rate, and internal resistance. Therefore, the development of cathode materials has always been the core of battery technology research and development.
[0004] The mainstream cathode materials on the market include lithium iron phosphate (LFP), lithium cobalt oxide (LCO), and ternary lithium (NCM). As people pay more and more attention to battery safety performance, lithium iron manganese phosphate (LFMP) materials with olivine structure have attracted widespread attention. By introducing manganese elements, the theoretical platform voltage of LMFP is increased to 4.1V, which enables it to meet the needs of high-energy-density batteries. However, LMFP exhibits low ionic conductivity (<1×10 -16 cm 2 ·s -1 ) and electronic conductivity (<1×10 -10 S cm -1 ), in order to improve this defect, material nano-sizing is usually used to increase its specific surface area to achieve the effect of improving conductivity.
[0005] However, an excessively high specific surface area will also bring about a series of challenges in the manufacturing process, such as material powder loss during the coating process, reduced electrode peeling force, increased electrode brittleness, and low compaction density. These problems not only increase the difficulty of battery manufacturing, but will also ultimately affect and damage or reduce the overall performance of the battery.
[0006] In summary, although LMFP has shown great potential as a new type of cathode material, it still faces challenges in practical applications, such as high process difficulty and the need to improve performance due to process problems. Therefore, targeted development is still needed to support the application and development of LMFP cathode materials. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a positive electrode plate and its preparation method and use, wherein the active layer of the positive electrode plate includes an active material, a conductive agent and a copolymer-modified binder, and the copolymer-modified binder includes PVDF-HFP. The present invention introduces a new binder polyvinylidene fluoride hexafluoropropylene, and uses its perfluorinated chain segment (-HFP) to effectively reduce the crystallinity of the binder, thereby increasing the specific surface area, providing greater adhesion for the plate, effectively improving the peeling force, improving the bending of the plate, and reducing the brittleness of the plate; solving the adverse effects of process problems on the performance of the positive electrode plate, and is particularly suitable for the preparation of positive electrode plates using nano-manganese iron lithium phosphate materials.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a positive electrode plate, wherein the active layer of the positive electrode plate comprises an active material, a conductive agent and a copolymer-modified binder, wherein the copolymer-modified binder comprises PVDF-HFP; based on the total mass of the active layer as 100%, the copolymer-modified binder accounts for 1% to 2%.
[0010] The present invention introduces a new type of binder, polyvinylidene fluoride-hexafluoropropylene, and uses its perfluorinated chain segment (-HFP) to effectively reduce the crystallinity of the binder, thereby increasing the specific surface area and providing greater adhesion for the pole piece. Compared with conventional PVDF binders, even when the usage is reduced, it can effectively improve the peeling force, improve the bending degree of the pole piece, and reduce the brittleness of the pole piece; and because PVDF-HFP has a high density of polarizable fluorinated groups and a high dielectric constant, its polar functional groups have a strong interaction with lithium ions, so it can promote the rapid transmission of lithium ions, uniform lithium ion flux, effectively reduce internal resistance, and improve the electrochemical performance of the positive pole piece. Considering that the current positive electrode formula designed for the LMFP system still uses the LFP system, the traditional polyvinylidene fluoride (PVDF) binder is no longer suitable for LMFP with small particle size and high specific surface area, and the present invention solves the adverse effects of process problems on the performance of the positive pole piece by using PVDF-HFP, so it is particularly suitable for the preparation of positive pole pieces with nano-manganese iron phosphate lithium active materials.
[0011] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] As a preferred technical solution of the present invention, the active material includes LMFP (lithium manganese iron phosphate).
[0013] It should be noted that the present invention does not specifically limit the specific material selection of the active material and the conductive agent, but due to the effect and characteristics of the scheme of the present invention, it is particularly suitable for the preparation of lithium manganese iron phosphate positive electrode sheets, but is also suitable for active materials and conductive agents selected and adjusted according to actual needs.
[0014] It should also be noted that the active layer of the positive electrode plate is disposed on a current collector. The present invention does not specifically limit the selection of the current collector, and it can be reasonably selected and adjusted according to actual needs.
[0015] Preferably, the particle size of the active material is 0.55-1.25 μm, for example, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, 1 μm, 1.05 μm, 1.1 μm, 1.15 μm, 1.2 μm or 1.25 μm, etc.
[0016] Preferably, the specific surface area of the active material is 23 to 27 m 2 / g, for example 23m 2 / g, 23.5m 2 / g, 24m 2 / g, 24.5m 2 / g, 25m 2 / g, 25.5m 2 / g, 26m 2 / g, 26.5m 2 / g or 27m 2 / g, etc.
[0017] Preferably, the compacted density of the active material is 1.9 to 2.6 g / cm 3 , for example 1.9 g / cm 3 , 1.95g / cm 3 , 2g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 , 2.15g / cm 3 , 2.2g / cm 3 , 2.25g / cm 3 , 2.3g / cm 3 , 2.35g / cm 3 , 2.4g / cm 3 , 2.45g / cm 3 , 2.5g / cm 3 , 2.55g / cm 3 or 2.6 g / cm 3 wait.
[0018] Preferably, the surface density of the active layer is 422-436 g / m 2 , for example 422g / m 2 , 423g / m 2 , 424g / m 2 , 425g / m 2 , 426g / m 2 , 427g / m 2 , 428g / m 2 , 429g / m 2 , 430g / m 2 , 431g / m 2 , 432g / m 2 , 433g / m 2 , 434g / m 2 , 435g / m 2 or 436g / m 2 wait.
[0019] Preferably, the thickness of the active layer is 170-180 mm, preferably 178-180 mm, for example, 170 mm, 171 mm, 172 mm, 173 mm, 174 mm, 175 mm, 176 mm, 177 mm, 178 mm, 179 mm or 180 mm.
[0020] In the present invention, based on the total mass of the active layer as 100%, the copolymer modified binder accounts for 1% to 2%, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc., preferably 1.5% to 2%.
[0021] Preferably, based on the total mass of the active layer as 100%, the active material accounts for 96.5% to 98%, for example, 96.5%, 96.8%, 97%, 97.3%, 97.5%, 97.8% or 98%, and the conductive agent accounts for 0.2% to 1.5%, for example, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.45% or 1.5%, etc.
[0022] Preferably, the number average molecular weight (Mn) of the copolymer modified binder is 100000-150000, for example, 100000, 103000, 105000, 108000, 110000, 112000, 115000, 118000, 120000, 123000, 125000, 127000, 130000, 132000, 135000, 138000, 140000, 142000, 145000, 148000 or more. the weight average molecular weight (Mw) is 400,000 to 500,000, for example, 400,000, 405,000, 410,000, 415,000, 420,000, 425,000, 430,000, 435,000, 440,000, 445,000, 450,000, 455,000, 460,000, 465,000, 470,000, 475,000, 480,000, 485,000, 490,000, 495,000 or 500,000, etc.
[0023] As a preferred technical solution of the present invention, the peeling force of the positive electrode sheet is 0.6-0.8N, for example, 0.6N, 0.62N, 0.64N, 0.66N, 0.68N, 0.7N, 0.72N, 0.74N, 0.76N, 0.78N or 0.8N.
[0024] Preferably, the interface resistance of the positive electrode sheet is 3 to 3.6 Ω / m 2 , for example 3Ω / m 2 、3.05Ω / m 2 , 3.1Ω / m 2 , 3.15Ω / m 2 , 3.2Ω / m 2 , 3.25Ω / m 2 , 3.3Ω / m 2 , 3.35Ω / m 2 , 3.4Ω / m 2 , 3.45Ω / m 2 , 3.5Ω / m 2 、3.55Ω / m 2 or 3.6Ω / m 2 wait.
[0025] Preferably, the DC internal resistance test value of the positive electrode plate is 40-45 mΩ, for example, 40 mΩ, 40.5 mΩ, 41 mΩ, 41.5 mΩ, 42 mΩ, 42.5 mΩ, 43 mΩ, 43.5 mΩ, 44 mΩ, 44.5 mΩ or 45 mΩ.
[0026] In a second aspect, the present invention provides a method for preparing a positive electrode plate according to the first aspect, comprising preparing PVDF-HFP and a first solvent into a glue solution, using the glue solution and an active material, a conductive agent and a second solvent to stir and slurry, coat and dry in sequence to obtain a positive electrode plate.
[0027] It should be noted that since the present invention solves the positive electrode plate manufacturing process problem by using PVDF-HFP, further adjustments to the methods, steps and parameters in the process can be made to play a greater optimization role in combination with PVDF-HFP, thereby achieving significant improvements in the plate peeling force, plate curvature and plate brittleness.
[0028] As a preferred technical solution of the present invention, based on the mass of the glue as 100%, the PVDF-HFP accounts for 6% to 9%, for example, 6%, 6.3%, 6.5%, 6.8%, 7%, 7.2%, 7.5%, 7.8%, 8%, 8.3%, 8.5%, 8.8% or 9%, etc.
[0029] Preferably, the first solvent comprises a main solvent and an additional solvent, the main solvent comprises NMP, and the additional solvent comprises TFA (trifluoroacetic acid).
[0030] In the present invention, since PVDF-HFP has a low crystallinity and is difficult to be dissolved by the traditional solvent NMP, it is preferred to introduce trifluoroacetic acid as a solvent on the basis of the traditional solvent. As a strong acid solvent, the introduction of a small amount of TFA can weaken the interaction between the polymer chains of the binder, making the polymer softer and improving the solubility of the polymer.
[0031] Preferably, based on the mass of the first solvent as 100%, the TFA accounts for 0.04% to 0.06%, for example, 0.04%, 0.042%, 0.044%, 0.046%, 0.048%, 0.05%, 0.052%, 0.054%, 0.056%, 0.058% or 0.06%, etc.
[0032] Preferably, the viscosity of the first solvent is 6000-7000 mPa·s, for example, 6000 mPa·s, 6100 mPa·s, 6200 mPa·s, 6300 mPa·s, 6400 mPa·s, 6500 mPa·s, 6600 mPa·s, 6700 mPa·s, 6800 mPa·s, 6900 mPa·s or 7000 mPa·s, etc., preferably 6400-6600 mPa·s, and more preferably 6500 mPa·s;
[0033] Preferably, the second solvent comprises NMP.
[0034] As a preferred technical solution of the present invention, the stirring pulping method includes any one of a wet stirring process, a dry stirring process or a wet and dry mixed stirring process, preferably a wet stirring process.
[0035] As a preferred technical solution of the present invention, the wet stirring process comprises:
[0036] (1) first stirring a portion of the active material, a conductive agent, and a second solvent;
[0037] (2) adding another portion of active material for a second stirring;
[0038] (3) increasing the stirring speed to perform a third stirring;
[0039] (4) adding the glue solution again and performing a fourth stirring;
[0040] (5) reducing the stirring speed and performing the fifth stirring;
[0041] (6) Adjusting the viscosity, completing the stirring and slurrying, and obtaining the slurry.
[0042] As a preferred technical solution of the present invention, the mass ratio of the active materials in step (1) to step (2) is 1:(0.5-2), for example, 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3, 1:1.5, 1:1.8 or 1:2, etc., preferably 1:1.
[0043] Preferably, the revolution speed of the first stirring in step (1) is 18 to 22 rpm, for example, 18 rpm, 19 rpm, 20 rpm, 21 rpm or 22 rpm, etc., the dispersion speed (rotation speed) is 0 to 5 rpm, for example, 0 rpm (no dispersion), 1 rpm, 2 rpm, 3 rpm, 4 rpm or 5 rpm, etc., and the time is 5 to 15 min, for example, 5 min, 7 min, 9 min, 11 min, 13 min or 15 min, etc.
[0044] Preferably, the revolution speed of the second stirring in step (2) is 13-17 rpm, for example, 13 rpm, 14 rpm, 15 rpm, 16 rpm or 17 rpm, etc., the dispersion speed (rotation speed) is 380-420 rpm, for example, 380 rpm, 390 rpm, 400 rpm, 410 rpm or 420 rpm, etc., and the time is 3-7 min, for example, 3 min, 4 min, 5 min, 6 min or 7 min, etc.
[0045] Preferably, the revolution speed of the third stirring in step (3) is 28-32 rpm, for example, 28 rpm, 29 rpm, 30 rpm, 31 rpm or 32 rpm, the dispersion speed (rotation speed) is 950-1050 rpm, for example, 950 rpm, 960 rpm, 970 rpm, 980 rpm, 990 rpm, 1000 rpm, 1010 rpm, 1020 rpm, 1030 rpm, 1040 rpm or 1050 rpm, and the time is 50-70 min, for example, 50 min, 52 min, 55 min, 58 min, 60 min, 63 min, 65 min, 68 min or 70 min, etc.
[0046] Preferably, the revolution speed of the fourth stirring in step (4) is 23-27 rpm, for example, 23 rpm, 24 rpm, 25 rpm, 26 rpm or 27 rpm, the dispersion speed (rotation speed) is 1400-1600 rpm, for example, 1400 rpm, 1420 rpm, 1440 rpm, 1460 rpm, 1480 rpm, 1500 rpm, 1520 rpm, 1540 rpm, 1560 rpm, 1580 rpm or 1600 rpm, and the time is 50-70 min, for example, 50 min, 53 min, 55 min, 58 min, 60 min, 63 min, 65 min, 68 min or 70 min, etc.
[0047] Preferably, the revolution speed of the fifth stirring in step (5) is 8 to 12 rpm, for example, 8 rpm, 9 rpm, 10 rpm, 11 rpm or 12 rpm, the dispersion speed (rotation speed) is 180 to 220 rpm, for example, 180 rpm, 1980 rpm, 200 rpm, 210 rpm or 220 rpm, and the time is 90 to 110 min, for example, 90 min, 92 min, 95 min, 98 min, 100 min, 103 min, 105 min, 108 min or 110 min, etc.
[0048] Preferably, the sixth stirring is performed when adjusting the viscosity in step (6), and the revolution speed of the sixth stirring is 8 to 12 rpm, for example, 8 rpm, 9 rpm, 10 rpm, 11 rpm or 12 rpm, etc., the dispersion speed (rotation speed) is 280 to 320 rpm, for example, 280 rpm, 290 rpm, 300 rpm, 310 rpm or 320 rpm, etc., and the time is 50 to 70 min, for example, 50 min, 53 min, 55 min, 58 min, 60 min, 63 min, 65 min, 68 min or 70 min, etc.
[0049] Exemplarily, the dry mixing process includes:
[0050] A1. All active materials and conductive agents are stirred for the seventh time; the revolution speed of the seventh stirring is 20-30 rpm, the dispersion speed is 450-550 rpm, and the time is 55-65 min;
[0051] A2, adding the second solvent NMP, and performing the eighth stirring; the revolution speed of the eighth stirring is 20-30 rpm, the dispersion speed is 750-850 rpm, and the time is 100-140 min;
[0052] A3, adding the glue solution again, and performing the ninth stirring; the revolution speed of the ninth stirring is 20-30 rpm, the dispersion speed is 1900-2100 rpm, and the time is 25-35 min;
[0053] A4, reduce the stirring speed and perform the tenth stirring; the revolution speed of the tenth stirring is 10-20rpm, the dispersion speed is 450-550rpm, and the time is 25-35min;
[0054] A5. Adjust the viscosity and perform the eleventh stirring, wherein the revolution speed of the eleventh stirring is 10-20 rpm, the dispersion speed is 450-550 rpm, and the time is 55-65 min. Complete the stirring and slurrying to obtain slurry.
[0055] Exemplarily, the wet and dry mixing process includes:
[0056] B1. All active materials, conductive agents and the second solvent NMP are stirred for the twelfth time; the revolution speed of the twelfth stirring is 25-35 rpm, the dispersion speed is 0-5 rpm, and the time is 5-15 min;
[0057] B2. Add another part of the glue solution and perform the thirteenth stirring; the revolution speed of the thirteenth stirring is 20-30 rpm, the dispersion speed is 550-650 rpm, and the time is 50-100 min;
[0058] B3, add the remaining glue solution and perform the fourteenth stirring; the revolution speed of the fourteenth stirring is 25-35rpm, the dispersion speed is 1900-2100rpm, and the time is 55-65min;
[0059] B4, reduce the stirring speed and carry out the fifteenth stirring; the revolution speed of the fifteenth stirring is 5-15rpm, the dispersion speed is 400-500rpm, and the time is 25-35min;
[0060] B5. Adjust the viscosity and perform the sixteenth stirring, wherein the revolution speed of the sixteenth stirring is 20-30 rpm, the dispersion speed is 550-650 rpm, and the time is 55-65 min. Complete the stirring and slurrying to obtain slurry.
[0061] Preferably, the mass ratio of the glue in step B2 to that in step B3 is 1:(0.8-1.2), for example, 1:0.8, 1:0.83, 1:0.85, 1:0.9, 1:0.92, 1:0.95, 1:1.1, 1:1.13, 1:1.15, 1:1.18 or 1:2, etc., preferably 1:1.
[0062] As a preferred technical solution of the present invention, the coating speed is 13-17 m / min, for example, 13 m / min, 14 m / min, 15 m / min, 16 m / min or 17 m / min.
[0063] Preferably, the drying temperature is 85-95°C, for example, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C or 95°C.
[0064] Preferably, the drying is carried out under blowing, and the wind speed of the blowing is 14-18 m / s, for example, 14 m / s, 14.5 m / s, 15 m / s, 15.5 m / s, 16 m / s, 16.5 m / s, 17 m / s, 17.5 m / s or 18 m / s.
[0065] As a preferred technical solution of the present invention, the preparation method comprises:
[0066] The method for preparing the positive electrode sheet comprises:
[0067] S1. PVDF-HFP and a first solvent are prepared into a glue solution, wherein the mass of the glue solution is 100%, and the PVDF-HFP accounts for 1% to 10%; the first solvent comprises a main solvent accounting for 99.94% to 99.96% by mass and an additional solvent trifluoroacetic acid of 0.04% to 0.06% by mass; the viscosity of the first solvent is 6000 to 7000;
[0068] S2. The glue solution is sequentially stirred with the active material, the conductive agent and the second solvent NMP to form a slurry, wherein the stirring slurry adopts a wet stirring process, and the wet stirring process comprises:
[0069] (1) 33% to 66% of the mass of the total active material is used as the first part to perform a first stirring with the conductive agent and the second solvent; the first stirring has a revolution speed of 18 to 22 rpm, a dispersion speed of 0 to 5 rpm, and a time of 5 to 15 min;
[0070] (2) all the active materials are added as the second part, and then a second stirring is performed; the second stirring has an orbital speed of 13 to 17 rpm, a dispersion speed of 380 to 420 rpm, and a time of 3 to 7 minutes;
[0071] (3) increasing the stirring speed to perform a third stirring; the revolution speed of the third stirring is 28 to 32 rpm, the dispersion speed is 950 to 1050 rpm, and the time is 50 to 70 min;
[0072] (4) adding the glue solution and performing a fourth stirring; the revolution speed of the fourth stirring is 23 to 27 rpm, the dispersion speed is 1400 to 1600 rpm, and the time is 50 to 70 min;
[0073] (5) reducing the stirring speed and performing a fifth stirring; the revolution speed of the fifth stirring is 8 to 12 rpm, the dispersion speed is 180 to 220 rpm, and the time is 90 to 110 min;
[0074] (6) adjusting the viscosity and performing a sixth stirring, wherein the revolution speed of the sixth stirring is 8 to 12 rpm, the dispersion speed is 280 to 320 rpm, and the time is 50 to 70 min, completing the stirring and slurrying to obtain a slurry;
[0075] S3. The obtained slurry is coated on the current collector aluminum foil at a speed of 13 to 17 m / min, and then dried by air blast at 85 to 95° C. and a wind speed of 14 to 18 m / s to obtain a positive electrode sheet.
[0076] In a third aspect, the present invention provides a lithium-ion battery comprising the positive electrode sheet described in the first aspect, or the positive electrode sheet obtained by the preparation method described in the second aspect.
[0077] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0078] The present invention introduces a new binder polyvinylidene fluoride hexafluoropropylene into the active layer of the positive electrode plate, and utilizes its perfluorinated chain segment (-HFP) to effectively reduce the crystallinity of the binder, thereby increasing the specific surface area, providing greater adhesion for the plate, effectively improving the peeling force, improving the bending degree of the plate, and reducing the brittleness of the plate; solves the process problems such as powder loss and cracking of the positive electrode plate and their adverse effects on the performance of the positive electrode plate, and at the same time can also play a role in the characteristics of the plate obtained by the traditional PVDF binder while ensuring a low content, effectively reducing the interface resistance of the plate and the internal resistance of the battery cell, improving the electrochemical performance of the battery cell, and increasing the overall capacity of the battery cell. It is particularly suitable for the preparation of positive electrode plates using nano-manganese iron lithium phosphate materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 It is a comparison chart of the peeling force test values of the positive electrode sheets obtained in Example 1 and Comparative Example 1.
[0080] Figure 2 It is a comparison chart of the peeling force test values of the positive electrode sheets obtained in Example 2 and Comparative Example 2.
[0081] Figure 3 It is a comparison chart of the peeling force test values of the positive electrode sheets obtained in Example 3 and Comparative Example 3.
[0082] Figure 4 It is a comparison chart of the interface resistance test values of the positive electrode sheets obtained in Example 1 and Comparative Example 1.
[0083] Figure 5 It is a comparison chart of the interface resistance test values of the positive electrode sheets obtained in Example 2 and Comparative Example 2.
[0084] Figure 6 It is a comparison chart of the interface resistance test values of the positive electrode sheets obtained in Example 3 and Comparative Example 3. DETAILED DESCRIPTION
[0085] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0086] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0087] Example 1
[0088] This embodiment provides a positive electrode plate, wherein the active layer of the positive electrode plate comprises an active material, a conductive agent and a copolymer modified binder; the active material is nano-manganese iron lithium phosphate with a particle size of 0.9 μm and a specific surface area of 25 m 2 / g, compacted density is 2.02g / cm 3 The conductive agent is SP; the copolymer modified binder is PVDF-HFP, which has a number average molecular weight of 130,000 and a weight average molecular weight of 450,000; the surface density of the active layer is 429 g / m 2 , with a thickness of 178 mm; taking the total mass of the active layer as 100%, the conductive agent is controlled to account for 1.2%, and the mass of the copolymer-modified binder is adjusted to account for 0.5%, 1%, 1.5%, 2% and 2.5% respectively, and the remainder is lithium manganese iron phosphate, to obtain five positive electrode sheets, which are numbered as Example 1-1, Example 1-2, Example 1-3, Example 1-4 and Example 1-5 respectively.
[0089] The method for preparing the positive electrode sheet comprises:
[0090] S1. PVDF-HFP and a first solvent are prepared into a glue solution, wherein the mass of the glue solution is 100%, and the PVDF-HFP accounts for 6%; the first solvent comprises a main solvent NMP accounting for 99.95% by mass and an additional solvent trifluoroacetic acid accounting for 0.05% by mass; the viscosity of the first solvent is 6500 mPa·s;
[0091] S2. The glue solution is sequentially stirred with the active material, the conductive agent and the second solvent NMP to form a slurry, wherein the stirring slurry adopts a wet stirring process, and the wet stirring process comprises:
[0092] (1) 50% of the mass of the total active material is used as the first part to perform a first stirring with the conductive agent and the second solvent; the first stirring is performed at a revolution speed of 20 rpm, a dispersion speed of 0 rpm, and a time of 10 min;
[0093] (2) taking another 50% by weight of the active material as the second part and adding it, and then performing a second stirring; the second stirring has a revolution speed of 15 rpm, a dispersion speed of 400 rpm, and a time of 5 min;
[0094] (3) increasing the stirring speed to perform a third stirring; the revolution speed of the third stirring is 30 rpm, the dispersion speed is 1000 rpm, and the time is 60 min;
[0095] (4) adding the glue solution again and performing a fourth stirring; the fourth stirring has an orbital speed of 25 rpm, a dispersion speed of 1500 rpm, and a time of 60 min;
[0096] (5) reducing the stirring speed and performing the fifth stirring; the revolution speed of the fifth stirring is 10 rpm, the dispersion speed is 200 rpm, and the time is 100 min;
[0097] (6) Adjust the viscosity and perform the sixth stirring, wherein the revolution speed of the sixth stirring is 10 rpm, the dispersion speed is 300 rpm, and the time is 60 min. The stirring and slurrying is completed to obtain a slurry.
[0098] S3. The obtained slurry is coated on the current collector aluminum foil at a speed of 15 m / min, and then dried by air blast at 90° C. and a wind speed of 16 m / s to obtain a positive electrode sheet.
[0099] Example 2
[0100] This embodiment provides a positive electrode plate, which is the same as that of Example 1, and based on the total mass of the active layer as 100%, the conductive agent is controlled to account for 1.2%, and the mass of the copolymer modified binder is adjusted to account for 0.5%, 1%, 1.5%, 2% and 2.5% respectively, and the remainder is lithium manganese iron phosphate, to obtain five positive electrode plates, which are numbered as Example 2-1, Example 2-2, Example 2-3, Example 2-4 and Example 2-5 respectively.
[0101] However, the stirring slurrying process in step S2 of the five preparation methods of the positive electrode sheets is different. In this embodiment, the stirring slurrying adopts a dry stirring process, and the dry stirring process includes:
[0102] A1. All active materials and conductive agents are stirred for the seventh time; the revolution speed of the seventh stirring is 25 rpm, the dispersion speed is 500 rpm, and the time is 60 min;
[0103] A2, adding the second solvent NMP, and performing the eighth stirring; the revolution speed of the eighth stirring is 25 rpm, the dispersion speed is 800 rpm, and the time is 120 min;
[0104] A3, adding the glue solution again, and performing the ninth stirring; the revolution speed of the ninth stirring is 25rpm, the dispersion speed is 2000rpm, and the time is 30min;
[0105] A4, reduce the stirring speed and perform the tenth stirring; the revolution speed of the tenth stirring is 15 rpm, the dispersion speed is 500 rpm, and the time is 30 min;
[0106] A5. Adjust the viscosity and perform the eleventh stirring, wherein the revolution speed of the eleventh stirring is 15 rpm, the dispersion speed is 500 rpm, and the time is 60 min. Complete the stirring and slurrying to obtain slurry.
[0107] Except for the above, other conditions are exactly the same as those in Example 1.
[0108] Example 3
[0109] This embodiment provides a positive electrode plate, which is the same as that of Example 1, and based on the total mass of the active layer as 100%, the conductive agent is controlled to account for 1.2%, and the mass of the copolymer modified binder is adjusted to account for 0.5%, 1%, 1.5%, 2% and 2.5% respectively, and the remainder is lithium manganese iron phosphate, to obtain five positive electrode plates, which are numbered as Example 3-1, Example 3-2, Example 3-3, Example 3-4 and Example 3-5 respectively.
[0110] However, the stirring slurrying process in step S2 of the five methods for preparing positive electrode sheets is different. In this embodiment, the stirring slurrying adopts a mixing stirring process, and the mixing stirring process includes:
[0111] B1. All active materials, conductive agents and the second solvent NMP are stirred for the twelfth time; the revolution speed of the twelfth stirring is 30 rpm, the dispersion speed is 0 rpm, and the time is 10 min;
[0112] B2, add 50% of the glue solution and perform the thirteenth stirring; the revolution speed of the thirteenth stirring is 25rpm, the dispersion speed is 600rpm, and the time is 90min;
[0113] B3, add the remaining glue solution and perform the fourteenth stirring; the revolution speed of the fourteenth stirring is 30rpm, the dispersion speed is 2000rpm, and the time is 60min;
[0114] B4, reduce the stirring speed and carry out the fifteenth stirring; the revolution speed of the fifteenth stirring is 10rpm, the dispersion speed is 450rpm, and the time is 30min;
[0115] B5. Adjust the viscosity and perform the sixteenth stirring, wherein the revolution speed of the sixteenth stirring is 25 rpm, the dispersion speed is 600 rpm, and the time is 60 min. Complete the stirring and slurrying to obtain slurry.
[0116] Except for the above, other conditions are exactly the same as those in Example 1.
[0117] Example 4
[0118] The present embodiment provides a positive electrode plate, which is the same as Embodiment 1-3 in Embodiment 1, that is, the mass proportion of the copolymer-modified adhesive is 1.5%, but the fourth stirring of step (4) in the wet stirring process of step S2 in the preparation method is adjusted, as shown in Table 1. Except for the above, other conditions are exactly the same as those in Embodiment 1.
[0119] Table 1
[0120] Positive electrode number Revolution speed (rpm) Dispersion speed (rpm) Time (min) Example 4-1 15 1000 60 Example 4-2 15 1000 90 Example 4-3 15 1500 60 Example 4-4 15 1500 90 Embodiment 4-5 25 1000 60 Embodiment 4-6 25 1000 90 Examples 1-3 25 1500 60 Embodiment 4-7 25 1500 90
[0121] Example 5
[0122] This embodiment provides a positive electrode plate, which is the same as that of Embodiments 1-3, that is, the mass proportion of the copolymer-modified adhesive is 1.5%, but the coating and drying of step S3 in the preparation method are adjusted, as shown in Table 2. Except for the above, other conditions are exactly the same as those in Embodiment 1.
[0123] Table 2
[0124] Positive electrode number Coating speed (m / min) Drying temperature (℃) Drying wind speed (m / s) Example 5-1 8 90 8 Example 5-2 8 90 16 Example 5-3 8 110 8 Example 5-4 8 110 16 Example 5-5 15 90 8 Examples 1-3 15 90 16 Embodiment 5-6 15 110 8 Embodiment 5-7 15 110 16
[0125] Example 6
[0126] This embodiment provides a positive electrode plate, which is the same as that of Embodiments 1-3, but the first solvent in step S1 in the preparation method is adjusted, as shown in Table 3. Except for the above, other conditions are exactly the same as those in Embodiment 1.
[0127] Table 3
[0128] Positive electrode number Main solvent ratio Added solvent ratio First solvent viscosity Comparative Example 4-1 100 0 8700 Example 6-1 99.98 0.02 7800 Examples 1-3 99.95 0.05 6500 Example 6-2 99.93 0.07 4300 Example 6-3 99.90 0.10 3500
[0129] Example 7
[0130] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 1-3, that is, the mass proportion of the copolymer-modified adhesive is 1.5%, but the particle size of the nano-sized lithium manganese iron phosphate is adjusted from 0.9 μm to 0.55 μm and 1.25 μm, respectively, to obtain two positive electrode plates, which are numbered as Embodiment 7-1 and Embodiment 7-2, respectively. Except for the above, other conditions are exactly the same as those of Embodiment 1.
[0131] Comparative Example 1
[0132] This comparative example provides a positive electrode sheet, wherein the positive electrode sheet uses a conventional PVDF binder to replace the copolymer modified binder PVDF-HFP, and based on the total mass of the active layer as 100%, the conductive agent is controlled to account for 1.2%, the mass of the conventional PVDF binder is adjusted to account for 0.5%, 1%, 1.5%, 2% and 2.5% respectively, and the remainder is lithium manganese iron phosphate, and five positive electrode sheets are obtained by a preparation method including a wet stirring process, and are numbered as comparative example 1-1, comparative example 1-2, comparative example 1-3, comparative example 1-4 and comparative example 4-5. Except for the above, the other conditions are exactly the same as those in Example 1.
[0133] Comparative Example 2
[0134] This comparative example provides a positive electrode sheet, wherein the positive electrode sheet uses a conventional PVDF binder to replace the copolymer modified binder PVDF-HFP, and based on the total mass of the active layer as 100%, the conductive agent is controlled to account for 1.2%, the mass of the conventional PVDF binder is adjusted to account for 0.5%, 1%, 1.5%, 2% and 2.5% respectively, and the remainder is lithium manganese iron phosphate, and five positive electrode sheets are obtained by a preparation method including a dry stirring process, and are numbered as comparative example 2-1, comparative example 2-2, comparative example 2-3, comparative example 2-4 and comparative example 2-5. Except for the above, the other conditions are exactly the same as those in Example 2.
[0135] Comparative Example 3
[0136] This comparative example provides a positive electrode sheet, wherein the positive electrode sheet uses a conventional PVDF binder to replace the copolymer modified binder PVDF-HFP, and based on the total mass of the active layer as 100%, the conductive agent is controlled to account for 1.2%, the mass of the conventional PVDF binder is adjusted to account for 0.5%, 1%, 1.5%, 2% and 2.5% respectively, and the remainder is lithium manganese iron phosphate, and five positive electrode sheets are obtained by a preparation method including a mixing and stirring process, and are numbered as comparative example 3-1, comparative example 3-2, comparative example 3-3, comparative example 3-4 and comparative example 3-5. Except for the above, the other conditions are exactly the same as those in Example 3.
[0137] Comparative Example 4
[0138] This comparative example provides a positive electrode sheet, which is the same as that of Example 1-3, but the first solvent in step S1 in the preparation method is adjusted, and no solvent is added to obtain positive electrode sheets, which are numbered as Comparative Example 4-1, as shown in Table 3. Except for the above, other conditions are exactly the same as those of Example 1.
[0139] Comparative Example 5
[0140] This comparative example provides a positive electrode plate, in which conventional PVDF binder is used instead of the copolymer modified binder PVDF-HFP to obtain two positive electrode plates, which are numbered as comparative example 5-1 and comparative example 5-2. Except for the above, other conditions are exactly the same as those in Example 7.
[0141] Characterization and Testing:
[0142] Ⅰ. Brittleness / bending test: Cut the cold-pressed positive electrode into a size of length*width=2*10mm, use a curvature tester to place the battery electrode to be tested on the fixture or test bench of the tester, and use a fixture to fix the ends to ensure uniform contact between the sample and the fixture; adjust the fixture or test bench as needed to put the sample in a suitable position and angle to ensure the accuracy and stability of the test; use a metal rod of Φ1~Φ12 (metal rod diameter 1~12mm) to fold the electrode from the middle, repeat three times, and set the test speed to 5mm / min; start the tester, start the battery electrode curvature test, record the data during the test, such as deformation and load, and observe whether there is powder loss;
[0143] Ⅱ. Peel force test: Use a peel force tester and prepare a flat thin steel plate with a length of about 200-300mm and a width of about 40-60mm. Paste a double-sided tape in the center of the steel plate, making sure that the length of the double-sided tape is greater than the sample test length and is the same width as the electrode. Smooth the double-sided tape with force to make it fit tightly in the center of the steel plate. Uncover the cover paper of the double-sided tape and paste the electrode on the tape. Make sure that the electrode and the tape are completely matched and fit to ensure that the width is consistent when testing the peel force. Otherwise, the test results may be inaccurate, and the peel curve may appear to jump or wave. Prepare a tensile machine and two clamps. Insert the steel plate with the fixed electrode into the lower clamp and fix it vertically; insert the unadhesive electrode into the upper clamp and fix it at 180° with the electrode of the lower clamp; calibrate and reset, set the test width to 10cm, the peel length to 15cm, and the speed to 20mm / mim; start the test to obtain the peel strength curve and average value. When processing the data, delete the two segments at the beginning and end of the test to obtain the standard curve.
[0144] Ⅲ. Internal resistance test:
[0145] First, make a battery: use a cutter to cut the cold-pressed positive and negative electrode sheets into electrode sheets with a length * width = 100mm * 150mm, and use a small stacking machine to stack the battery cells, with 19 layers of positive electrodes and 20 layers of negative electrodes; then use a hot press to hot-press, and the hot pressing parameters are: pressure 1t, time 30s, temperature 90℃; then install it in an aluminum-plastic film and inject 30g of liquid; use a constant current of 0.5A to charge for 120min, then use a constant current of 5A to charge for 54min, and then seal it after charging; let the battery cell stand at 45℃ for 12h, then use a constant current of 3.3A to charge for 82min, and use a constant current of 3.3A to discharge for 144min, and the battery cell is completed.
[0146] DCIR test method: connect the offline battery cell to the charge and discharge test cabinet, record the open circuit voltage OCV1, then use a constant current of 10A to discharge for 30s, let it stand for 5min, and record the open circuit voltage OCV2. DCIR = (OCV1-OCV2) / 10A, and calculate it.
[0147] It should be noted that there is a certain difference between the brittleness of the electrode and the peeling force performance. Brittleness mainly refers to the bonding ability between the active materials in the electrode, while the peeling force refers to the maximum force required to peel the material per unit width, which is used to reflect the bonding effect between the active material on the battery electrode and the copper / aluminum current collector. The two characteristics reflect different abilities.
[0148] Figure 1 , Figure 2 and Figure 3 1 is a comparison chart of the test results of the peeling force of the positive electrode sheets obtained in Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3; Figure 1 , Figure 2 and Figure 3 The peeling force data shows that the peeling force gradually increases with the increase of binder content, but the growth of the positive electrode sheet with PVDF-HFP as the binder is nonlinear. When the binder content is greater than 1.5%, the growth rate slows down. Based on this, the effect of the mixing process on the peeling force is compared, and it is found that for the peeling force, the wet process > the mixed process > the dry process; and by comparing PVDF-HFP and PVDF, it is found that the introduction of PVDF-HFP can significantly increase the peeling force of the electrode sheet, which is due to the introduction of -HFP, which reduces the crystallinity of the binder.
[0149] Figure 4 , Figure 5 and Figure 6 is a comparison chart of the test results of the interface resistance of the positive electrode sheets obtained in Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3; Figure 4 , Figure 5 and Figure 6 The interface resistance data shows that the interface resistance gradually decreases with the increase of binder content. Based on this, the interface resistance of the stirring process is compared, and it is found that for the interface resistance, the wet process is less than the mixed process and the dry process is less; by comparing PVDF-HFP and PVDF, it is found that the introduction of PVDF-HFP can reduce the interface resistance, which is because the -HFP chain segment gives it a higher dielectric constant, thereby reducing the interface resistance of the electrode.
[0150] Table 4 is the curvature test results of the positive electrode sheets obtained in Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3. It can be seen that the curvature value of the electrode sheet using PVDF-HFP as a binder is significantly lower than that of the electrode sheet using PVDF as a binder, indicating that the introduction of PVDF-HFP can give the electrode sheet greater bending performance, reduce the powder loss of the electrode sheet, and increase the stability of the electrode.
[0151] Table 4
[0152]
[0153]
[0154] Based on the performance of stripping force, interface resistance and curvature, it is determined that the best solution for using PVDF-HFP is Example 1-3, and the best solution for using PVDF is Comparative Example 1-4. The two are then assembled into soft-pack batteries for internal resistance comparison. It is found that the DCIR of the battery containing the positive electrode sheets of Examples 1-3 at 50% SOC is 42.58mΩ, while the battery containing the positive electrode sheets of Comparative Example 1-4 is as high as 63.17mΩ, which is a significant improvement. This is attributed to the high density of polarizable fluorinated groups in the -HFP segment, and its polar functional groups have a strong interaction with lithium ions, which can promote rapid lithium ion transmission, uniform lithium ion flux, and reduce internal resistance. Based on the above data, the electrode characteristics of PVDF-HFP and PVDF are compared, and it can be determined that after the introduction of PVDF-HFP, the electrode's stripping force, interface resistance, DCIR and other characteristics can have better performance relative to PVDF.
[0155] The above analysis and test results of the positive electrode sheets obtained in other embodiments and comparative examples are shown in Table 5.
[0156] Table 5
[0157]
[0158]
[0159] Furthermore, by comparing the test results of the positive electrode sheet obtained in Example 4 in Table 1 with the positive electrode sheet of Examples 1-3, it is found that the use of a suitable wet stirring process can ensure the improvement of the peeling force, and improve the bending and brittleness, and the wet stirring process of Examples 1-3 is determined to be the best;
[0160] Furthermore, by comparing the test results of the positive electrode sheet obtained in Example 5 in Table 1 with the positive electrode sheets of Examples 1-3, it was found that the coating and drying processes also affect the performance of the obtained positive electrode sheets to a certain extent, and the wet stirring process of Example 1-3 was determined to be the best.
[0161] Furthermore, by comparing the test results of the positive electrode sheets obtained in Example 6 and Comparative Example 4 in Table 1 with the positive electrode sheets of Examples 1-3, it was found that the proportion of added solvent would affect the state of the glue after stirring. If the proportion of added solvent is too low, the binder will be unevenly dispersed, the viscosity will be too high, and the distribution in the electrode sheet will be uneven, thereby affecting the peeling force, internal resistance and other properties of the electrode sheet; if the proportion of added solvent is too high, the overall viscosity of the glue will be reduced, thereby affecting the uniformity of coating.
[0162] Furthermore, by comparing the test results of the positive electrode sheets obtained in Example 7 and Comparative Example 5 in Table 1 with the positive electrode sheets of Examples 1-3, it is found that the size of the LMFP particle size directly affects the state of the electrode sheet resistance, peeling force and curvature. If the particle size is too small and the specific surface area increases, more binder is required to ensure the peeling performance of the electrode sheet. If the binder ratio remains unchanged, the peeling force and curvature will be greatly reduced; if the particle size is too large, the required binder is too small, but the interface resistance of the electrode sheet and the DCIR of the battery cell will increase, affecting its electrical performance. The PVDF-HFP of the present invention is more suitable for preparing positive electrode sheets for nano-manganese iron phosphate lithium materials.
[0163] From the above, it can be seen that the present invention introduces a new binder polyvinylidene fluoride hexafluoropropylene into the active layer of the positive electrode plate, and utilizes its perfluorinated chain segment (-HFP) to effectively reduce the crystallinity of the binder, thereby increasing the specific surface area, providing greater adhesion for the plate, effectively improving the peeling force, improving the bending degree of the plate, and reducing the brittleness of the plate; it solves the process problems such as powder loss and cracking of the positive electrode plate and their adverse effects on the performance of the positive electrode plate, and at the same time, it can also play a role in the characteristics of the plate obtained by the traditional PVDF binder while ensuring a low content, effectively reducing the interface resistance of the plate and the internal resistance of the battery cell, improving the electrochemical performance of the battery cell, and improving the overall capacity of the battery cell. It is particularly suitable for the preparation of positive electrode plates using nano-manganese iron phosphate lithium materials.
[0164] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0165] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0166] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A positive electrode sheet, characterized in that: The active layer of the positive electrode plate includes active materials, conductive agents and copolymer modified binders, wherein the copolymer modified binder includes PVDF-HFP; based on the total mass of the active layer being 100%, the copolymer modified binder accounts for 1% to 2%.
2. The positive electrode sheet according to claim 1, characterized in that: The active material includes LMFP; Preferably, the particle size of the active material is 0.55 to 1.25 μm; Preferably, the specific surface area of the active material is 23 to 27 m 2 / g; Preferably, the compacted density of the active material is 1.9 to 2.6 g / cm 3 ; Preferably, the surface density of the active layer is 422-436 g / m 2 ; Preferably, the thickness of the active layer is 170-180 mm, preferably 178-180 mm; Preferably, based on the total mass of the active layer being 100%, the copolymer-modified binder accounts for 1.5% to 2%; Preferably, based on the total mass of the active layer being 100%, the active material accounts for 96.5% to 98%, and the conductive agent accounts for 0.2% to 1.5%; Preferably, the number average molecular weight of the copolymer modified binder is 100,000 to 150,000, and the weight average molecular weight is 400,000 to 500,000.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The peeling force of the positive electrode sheet is 0.6-0.8N; Preferably, the interface resistance of the positive electrode sheet is 3 to 3.6 Ω / m 2 ; Preferably, the DC internal resistance test value of the positive electrode plate is 40-45 mΩ.
4. A method for preparing a positive electrode sheet according to any one of claims 1 to 3, characterized in that: The method comprises preparing PVDF-HFP and a first solvent into a glue solution, using the glue solution, an active material, a conductive agent and a second solvent to sequentially stir and slurry, coat and dry to obtain a positive electrode sheet.
5. The method for preparing a positive electrode sheet according to claim 4, characterized in that: Based on the mass of the glue solution being 100%, the PVDF-HFP accounts for 6% to 9%; Preferably, the first solvent comprises a main solvent and an additional solvent, the main solvent comprises NMP, and the additional solvent comprises TFA; Preferably, based on 100% by mass of the first solvent, the TFA accounts for 0.04% to 0.06%; Preferably, the viscosity of the first solvent is 6000-7000 mPa·s, preferably 6400-6600 mPa·s, and more preferably 6500 mPa·s; Preferably, the second solvent comprises NMP.
6. The method for preparing a positive electrode sheet according to claim 4 or 5, characterized in that: The stirring pulping method includes any one of a wet stirring process, a dry stirring process or a wet and dry mixed stirring process, preferably a wet stirring process.
7. The method for preparing a positive electrode sheet according to claim 6, characterized in that: The wet mixing process comprises: (1) first stirring a portion of the active material, a conductive agent, and a second solvent; (2) adding another portion of active material for a second stirring; (3) increasing the stirring speed to perform a third stirring; (4) adding the glue solution again and performing a fourth stirring; (5) reducing the stirring speed and performing the fifth stirring; (6) Adjusting the viscosity, completing the stirring and slurrying, and obtaining the slurry.
8. The method for preparing a positive electrode sheet according to claim 7, characterized in that: The mass ratio of the active material in step (1) to that in step (2) is 1:(0.5-2), preferably 1:1; Preferably, in step (1), the revolution speed of the first stirring is 18 to 22 rpm, the dispersion speed is 0 to 5 rpm, and the time is 5 to 15 min; Preferably, in step (2), the second stirring speed is 13-17 rpm, the dispersion speed is 380-420 rpm, and the time is 3-7 min; Preferably, the revolution speed of the third stirring in step (3) is 28-32 rpm, the dispersion speed is 950-1050 rpm, and the time is 50-70 min; Preferably, the revolution speed of the fourth stirring in step (4) is 23-27 rpm, the dispersion speed is 1400-1600 rpm, and the time is 50-70 min; Preferably, the revolution speed of the fifth stirring in step (5) is 8 to 12 rpm, the dispersion speed is 180 to 220 rpm, and the time is 90 to 110 min; Preferably, the sixth stirring is performed when adjusting the viscosity in step (6), and the revolution speed of the sixth stirring is 8 to 12 rpm, the dispersion speed is 280 to 320 rpm, and the time is 50 to 70 min.
9. The method for preparing a positive electrode sheet according to any one of claims 4 to 8, characterized in that: The coating speed is 13-17 m / min; Preferably, the drying temperature is 85-95°C; Preferably, the drying is carried out under blowing, and the wind speed of the blowing is 14-18 m / s.
10. A lithium ion battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 3 or a positive electrode sheet obtained by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Slurry, preparation method for electrode plates comprising slurry, and preparation method for lithium ion battery cell comprising electrode plates
CN106505187A
Electrode plate and electrochemical energy storage device
CN109461935A
Preparation method of lithium battery positive electrode slurry
CN109786740A
Positive pole piece as well as preparation method and application thereof
CN117766684A
Process for the production of electrode foils for galvanic elements
DE10125616A1